The acceptance and nutrients of traditional food “enbal” from Kei Islands - B. B. Tumiwa; E. J. Tapotubun (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
"Enbal" is one of the traditional foods from Kei Islands (Southeast Maluku Regency and Tual Town), which is made from cassava. This traditionally processed food has been known for generations. This product contains high carbohydrate but very low other nutritional values. One effort to improve the nutritional content of enbal is by the addition of fish flour to the process of fish enbal making. Round scad fish, the biggest catch result in Maluku, are used for making fish enbal. Research on round scad fish enbal has never been done before. Therefore, it is necessary to study about it, especially its formulation and nutritional value.The objectives of this study were to  determine the concentration of fish content in round scad fish enbal both chemically and organoleptically. Enbal fish with various concentration having the quality of being good with resources take the panel ranges between neutral until like. Formulations enbalbuyes is based on the method chosen by the addition of flour fish 15 %.